Developing Agricultural Complex as a basis for determining competitive economy specialization in Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
The agricultural sector combines all the branches of the economy participating in farm commodity producing, processing and selling. Its significance lies not only in providing food security of the state but also in affecting employment of the population and the whole national productive efficiency.Due to its inherent natural, climatic and geographical features as well as specific conditions and traditional work skills of local population, Kazakhstan has long been considered to beone of the world largest livestock producers. Nearly half of the populationin Kazakhstan isrepresentedbycountry people though the agricultural sector has become one of the weakest points requiring the appropriate and consistent approach to reforming. Currently the livestock takes more than 52% in the Kazakhstan’s structure of the value of gross agricultural output.Live stocken tailsa multiplicative effecton the economy including meet processing, woolprocessing (yarn, textiles,and clothes), leather processing (footwear, furniture, etc.), crop production diversification and a profound social effect (whole year employment, including the female population, and increase of rural income). There by the definition of competitive specialization of economy based on nation agriculture diversificationis a significant direction in Kazakhstan.Kazakhstan, due to its inherent natural, climatic and geographical features, as well as having specific conditions and traditional labor skills of the indigenous population, has long been considered one of the largest livestock countries. In Kazakhstan, nearly half the population lives in rural areas, but that agriculture was the weakest sector, which requires a properly sized coherent approach to reform.
Keywords: agricultural sector; agriculture; livestock sector; agricultural diversification; competitive specialization